Evaluation of High-Frequency Prediction Approaches in Price Determination on Financial Markets - Rahmouni, Abdelghani; Mansouri, Mohamed; Malainine, Cheklekbire (European Public & Social Innovation Review, 2025)
Introduction: This communication examines the impact of high-frequency trading (HFT) and algorithmic trading on financial markets. HFT utilizes sophisticated algorithms for ultra-fast transactions, optimizing profits and minimizing risks. Methodology: The study explores how HFT contributes to market efficiency and liquidity while also highlighting the risks of increased volatility, particularly during periods of market stress. Results: HFT algorithms improve liquidity but can amplify price fluctuations, challenging investors and financial institutions. These effects can create instability, especially in volatile market conditions. Discussion: The communication stresses the need for regulations to balance the benefits of HFT—such as efficiency and liquidity—against the risks posed by increased market volatility. Conclusions: While HFT offers significant benefits for financial markets, ongoing study and regulation are essential to ensure the stability and integrity of these markets.